PERCOBAAN PENGGUNAAN PESTISIDA UNTUK MENCEGAH SERANGAN JAMUR PEWARNA PADA ROTAN - Dominicus Martono (Jurnal Penelitian Hasil Hutan, 1990)
Sapstain fungi are the common fungi attacking fresh cut rattan which cause serious  economic deterioration.  The pattern of  sapstain  infestation on  fresh cut rattan and its prevention  were   studied in  rattan  processing industries at Cirebon.The material used consisted of fresh cut rattan  of semambu (Calamus scipionum  Burr) and seel (Daemonorop sp), measuring 30 cm long. Five pesticides were tested on rattan for sapstain protection. The staining percentage was inspected fomightly for two  months, whereas  the pattern of  fungal attack was inspected weekly  for one month. The  data were completely randomised design analysed and  tested by Dunnet  procedure at level 1% and 5%. The degree of staining  defect was transformed  into  arcsin √%.The result showed that semambu and seel were susceptible to sapstain. The initial  infestation starts  when  the rattan is freshly cut,  indicating  by the staining on  the cutting  surface. The  fungi  mycelia penetrate through parenchym-cell and tenninate in the nodes.  The rate of penetration  fungi  mycelium  is approximately  6 cm per week.The TCMTB/MTC, Thiobendazol + IF 1000 and MBT pesticides were found  effective   to prevent sapstain on fresh cut rattan.